Effect of Deformation by Wire Drawing on the Mechanical and Electrical Properties of Aluminum - Lazhar Yahia; Fatima Zohra Benlahreche; Wahid Kaddouri; Elamine Nouicer; Sihem Abderrahmane; Lyamine Briki; Mosbah Zidani (Science and Technology Indonesia, 2026)
This research investigates the influence of cold wire drawing on the electromechanical properties of high-purity (99.7%) aluminum conductors. Aluminum wires were subjected to progressive plastic deformation, with cross-sectional reduction rates ranging from 11.25% to 88.44%. The results demonstrate that mechanical deformation significantly enhances the ultimate tensile strength, reaching a peak value of 116.14 MPa and a Vickers hardness of 57.63 HV at the maximum reduction rate. Conversely, a marked reduction in elongation at break was observed, indicating a loss of ductility due to intense work hardening. Regarding electrical performance, the study reveals that electrical resistivity increases by only 0.87% over the full deformation range, while electrical conductivity exhibits a proportional decline. This degradation in transport properties is physically attributed to the increased density of lattice defects (dislocations) acting as electron scattering centers. These findings highlight the critical trade-off between mechanical reinforcement and electrical efficiency, providing essential data for the optimization of high-performance conductors for power transmission.